Risk of Switch to Mania/Hypomania in Bipolar Depressive Patients Treated with Antidepressants: A Real-World Study - Lei Feng; Weiwei Wang; Can Yin; Jing Li; Xinwei Zhang; Xiaotian Chang; Zizhao Feng; Mui Van Zandt; Seng Chan You; Sarah Seager; Christian Reich; Siyan Zhan; et al. (Health Data Science)
Background: The use of antidepressants in the treatment of bipolar depression remains controversial due to concerns about their potential to induce mood polarity switches. This multinational observational study aims to examine the association between the use of antidepressants and the risk of hypomanic/manic switch among bipolar depressive patients. Methods: Four electronic health record databases (IQVIA Disease Analyzer Germany, IQVIA Disease Analyzer France, IQVIA US Hospital Charge Data Master, and Beijing Anding Hospital) and one administrative claims database (IQVIA US Open Claims) were analyzed, and the study period covered from January 2013 until December 2017. Treatment patterns of patients with bipolar depression were collected. The hazard ratio (HR) was calculated by comparing the incidence of hypomanic/manic switch in patients who received antidepressants (AD group) with that in those who did not receive any antidepressant (non-AD group) in 730 days after the date of the first diagnosis of bipolar depression. Results: The analysis included a total of 122,843 patients from the 5 databases; 60.6% of them received antidepressants for bipolar depression. Across the 5 data sources, the mean age at index date ranged from 37.50 (15.72) to 52.10 (16.22) years. After controlling potential confounders by propensity score matching, the AD group’s manic switch risk was not significantly higher than the non-AD group’s (HR 1.04 [95% CI, 0.96 to 1.13]; P = 0.989). Additionally, no statistically significant difference was observed between patients prescribed antimanic drugs and those who were not (HR 0.69 [95% CI, 0.38 to 1.25]; P = 0.535). Conclusions: This study indicated that antidepressants were widely used in clinical settings for managing bipolar depression. The use of antidepressants was not associated with the risk of mania/hypomania switch when compared to non-antidepressants treatment. Therefore, antidepressants could be considered a treatment option for bipolar depression.